The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/coatings7080131
|View full text |Cite
|
Sign up to set email alerts
|

A Study of CO2 Laser Treatment on Colour Properties of Cotton-Based Fabrics

Abstract: Abstract:In this study, laser was applied to two types of cotton-based woven fabrics in order to study the effect of CO 2 laser technology on colour and fabric strength properties. The woven fabrics had different fibre compositions, i.e., one was 100% cotton while the other had 60% cotton blended with 40% polyester. They were treated with different combinations of laser processing parameters, i.e., resolution (52, 60, and 68 dpi) and pixel time (110, 120, 130, and 140 µs). There were two approaches adopted: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…This change in wettability may be due to the introduction of hydrophilic functional groups on the carbon fibre surface. Those hydrophilic functional groups may be the oxygen-containing functional groups [13]. Since laser treatment was conducted in atmospheric conditions, the high laser irradiation energy together with the ambient oxygen introduce oxygen-containing functional groups to the carbon fibre fabric surface as shown in Figure 8.…”
Section: Contact Anglementioning
confidence: 99%
See 1 more Smart Citation
“…This change in wettability may be due to the introduction of hydrophilic functional groups on the carbon fibre surface. Those hydrophilic functional groups may be the oxygen-containing functional groups [13]. Since laser treatment was conducted in atmospheric conditions, the high laser irradiation energy together with the ambient oxygen introduce oxygen-containing functional groups to the carbon fibre fabric surface as shown in Figure 8.…”
Section: Contact Anglementioning
confidence: 99%
“…Due to the increasing concerns on environmental protection issue, CO 2 laser treatment is a method for surface treatment which is based purely on physical interaction between the laser and the material surface [8][9][10][11][12]. Previous studies reveal that CO 2 laser treatment is a good candidate for changing aesthetic properties of materials in fabric form [13][14][15]. With careful control of CO 2 laser treatment process parameters, the aesthetic effects (surface textual effects) can be controlled with minimum damage of the material itself [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the tensile strength (warp direction) for heavyweight fabrics were higher than lightweight fabrics. Generally, the loss of strength is more in warp direction than weft, which is confirmed when laser pulse increases [21,23]. The tensile strength depends on fibers, yarns, and fabric [40].…”
Section: Evaluation Of Tensile Strength and Thicknessmentioning
confidence: 99%
“…Owing to these developments, researchers studied various laser variations or equipment to produce surface effects as the process was environmentally friendly compared to conventional methods [17]. Some studies [17,22,23] reported the effect of laser treatment on denim fabrics using pixel time and dots per inch (dpi) as one of the main parameters determining the colour contrast difference between pristine denim and treated denim and affecting other physical properties of the fabric.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already been conducted and reported the overall suitability and feasibility of the laser engraving on the textile materials [19,25,26,27,28]. The potential changes in the color and mechanical properties of the denim due to the laser engraving process have extensively been studied in previous studies [13,18,24,29]. Besides, Juciene et al studied the effect of the technological parameters of CO 2 laser on the color of indigo-dyed denim [30].…”
Section: Introductionmentioning
confidence: 99%